In Vitro Comparative Quality Assessment of Different Brands of Doxycycline Hyclate Finished Dosage Forms: Capsule and Tablet in Jimma Town, South-West Ethiopia - Abraham, Woldemichael (Adv Pharmacol Pharm Sci, 2021)
BACKGROUND: Persistent postmarket quality evaluation helps produce clear information on the current quality status of the different brands of a given drug and hence introduces a biopharmaceutical and therapeutically equivalent list of the products to the prescribers and users of it. This in turn facilitates access to essential medicines by breaking the high-cost barrier imposed by a few expensive brands of the product. This study was aimed at determining the quality and evaluating the equivalence of doxycycline hyclate capsules and tablets in Jimma, Ethiopia. METHODS: Ten brands of doxycycline hyclate capsules and tablets were tested for product identity, dosage uniformity, assay, and in vitro dissolution; and tablets were tested for friability and hardness. RESULTS: All investigated brands of doxycycline complied with the USP for dosage uniformity, an assay of the active ingredient, and single-point dissolution tests. One brand, D09, failed both hardness and friability tests. Comparisons of dissolution profiles applying fit factors confirmed that only brands D04, D06, and D07 had similarities with the innovator. Ratio test approaches also showed that significant variability exists between test products and comparators. Weibull model was found to provide the best adjustment curve for all brands, from model-dependent approaches employed for explaining the overall release of drug from the dosage forms. CONCLUSIONS: Doxycycline is a biowaiver product. Hence, in vitro dissolution evaluation suffices its market approval. In this quality assessment study, however, the samples passed quality control tests, except D09 brand which failed friability; it has been revealed that five out of eight brands had problems with interchangeability. Only three doxycycline hyclate brands were found to be equivalent to the comparators.